Emerging Positive Organizational Behavior - Luthans, Fred; Youssef, Carolyn M. (Journal of Management, 2007)
Although the value of positivity has been assumed over the years, only recently has it become a major focus area for theory building, research, and application in psychology and now organizational behavior. This review article examines, in turn, selected representative positive traits (Big Five personality, core self-evaluations, and character strengths and virtues), positive state-like psychological resource capacities (efficacy, hope, optimism, resiliency, and psychological capital), positive organizations (drawn from positive organization scholarship), and positive behaviors (organizational citizenship and courageous principled action). This review concludes with recommendations for future research and effective application.